2021
DOI: 10.1186/s12886-021-02039-6
|View full text |Cite
|
Sign up to set email alerts
|

Atomic force microscopy comparative analysis of the surface roughness of two posterior chamber phakic intraocular lens models: ICL versus IPCL

Abstract: Background To compare the anterior surface roughness of two commercially available posterior chamber phakic intraocular lenses (IOLs) using atomic force microscopy (AFM). Methods Four phakic IOLs were used for this prospective, experimental study: two Visian ICL EVO+ V5 lenses and two iPCL 2.0 lenses. All of them were brand new, were not previously implanted in humans, were monofocal and had a dioptric power of − 12 diopters (D). The anterior surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
6
1
Order By: Relevance
“…The anterior surface of the IPCL was significantly smoother than that of the ICL. [18] In our study, the OOQ-related values measured by the OQAS showed no significant differences between the 2 groups. It demonstrated that the amount of light scattered at the surface of the IOL is determined by the IOL surface roughness pertaining to the optical point of view.…”
Section: Discussioncontrasting
confidence: 45%
See 4 more Smart Citations
“…The anterior surface of the IPCL was significantly smoother than that of the ICL. [18] In our study, the OOQ-related values measured by the OQAS showed no significant differences between the 2 groups. It demonstrated that the amount of light scattered at the surface of the IOL is determined by the IOL surface roughness pertaining to the optical point of view.…”
Section: Discussioncontrasting
confidence: 45%
“…It demonstrated that the amount of light scattered at the surface of the IOL is determined by the IOL surface roughness pertaining to the optical point of view. [18] Our findings indicate that differences in surface roughness does not result in considerable clinical differences. The high-order aberrations were higher in LASIK than in phakic IOL implantation, and the phakic IOL group had better OOQ parameters than the LASIK group.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations